2015
DOI: 10.1111/jphd.12121
|View full text |Cite
|
Sign up to set email alerts
|

Fluoride concentrations of milk, infant formulae, and soy‐based products commercially available in Brazil

Abstract: The results suggest that the consumption of some brands of infant formulae, powdered milk, and soy-based milk in the first year of age could increase the risk of dental fluorosis, reinforcing the need for periodic surveillance of the F content of foods and beverages typically consumed by young children.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
4
1
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 24 publications
2
4
1
1
Order By: Relevance
“…Some groups have performed preliminary studies on the fluoride content of the soy milk beverages. In a recent study by Nagata et al 22 , soy milks available in Brazil were found to have an average fluoride concentration of 2.52 ppm, which is significantly higher than concentrations found in the present study (0.18 ppm). Conversely, fluoride concentrations of soy milks available in the United Kingdom have an average fluoride concentration of 0.29 ppm 26 , which is similar to the findings of the current study.…”
Section: Discussioncontrasting
confidence: 85%
See 1 more Smart Citation
“…Some groups have performed preliminary studies on the fluoride content of the soy milk beverages. In a recent study by Nagata et al 22 , soy milks available in Brazil were found to have an average fluoride concentration of 2.52 ppm, which is significantly higher than concentrations found in the present study (0.18 ppm). Conversely, fluoride concentrations of soy milks available in the United Kingdom have an average fluoride concentration of 0.29 ppm 26 , which is similar to the findings of the current study.…”
Section: Discussioncontrasting
confidence: 85%
“…The highest fluoride concentrations were found in almond milks (with the exception of MPC) and the cashew milks and the least fluoride concentrations were found in rice milk (RDR) and pecan milk (MMP). Bovine whole milk (COW) possesses relatively low amount of fluoride which is well documented in the literature 21 and consistent with some of the recent studies 22 . The results also demonstrated that major differences exist between different brands and between products with or without addition of other ingredients and/or flavors.…”
Section: Discussionsupporting
confidence: 81%
“…These data and studies previously published by various authors [ 30 , 31 , 32 ] indicate that soybean beverages may have a high content of fluoride, favoring dental fluorosis as a consequence of use of water for its manufacture. Thus, the need to determine the fluoride content in marketed soy beverages is established.…”
Section: Introductionsupporting
confidence: 80%
“…The samples of powdered soybean beverages for infants analyzed by de Carvalho et al [ 30 ] contained a fluoride concentration between 0.03 and 0.50 mg/L. Studies carried out by Nagata et al [ 31 ] registered higher fluoride concentrations in soybean beverage lyophilizates compared to the rest of the authors, as is the case of the SoyMilke brand (7.18 mg/L). In general, the concentrations recorded in the present study (2022) are higher than previously published data.…”
Section: Resultsmentioning
confidence: 99%
“…The growing rates of globalisation and technological advancements have contributed to the increased consumption of a diverse range of commercially prepared ready-to-eat (RTE) infant products [ 19 ]. Globally, several studies have reported a varied level of fluoride concentration in RTE infant and children’s foods and/or drink products [ 19 , 20 , 21 , 22 , 23 , 24 , 25 ]. For example, a study from Iran [ 20 ] reported the mean fluoride content between 1.32–2.36 (standard deviation (SD) 0.1–0.3) μg F/g in collected samples of infant powdered milk products.…”
Section: Introductionmentioning
confidence: 99%